Growing plants on the moon : a design concept pre-study for the lunar South Pole - Larsson, Rasmus (2008)
This master thesis in space engineering is a result of collaboration between Lulea University of Technology and NASA Ames Research Center, CA. Since the space shuttles stop to fly 2010 and NASA has planned to have a human base on the moon by 2020 there is both a gap in commercial interest and a massive amount of preparations that need to be done for the lunar base. One thing that is of interest for both NASA and the public is the ability to grow plants on the moon. A successful plant growth mission on the moon would generate massive publicity and be an important step towards a human base on the moon, and in the future Mars. This master thesis is a pre-study for a plant growth module concept to put on the lunar South Pole. The South Pole conditions are very favorable because the sun will be up for at least 6 months. At the same time the sunlight will need to be mirrored down to the plants, since they would not grow correctly if the incoming light angle is almost horizontal. A design has been made and different materials have been considered in this pre-study, with the purpose to see if it theoretically could be possible to grow a generation of genetically designed Arabidopsis thaliana plants in a plant growth module on the moon. We want them to grow and see if they are able to produce a second generation plants and monitor what kind of genes that are affected by the lunar conditions. It is found that placing a plant growth chamber on the South Pole could be possible, although there are many uncertainties and the design is very sensitive to changes in the materials. The plant growth module is small, which makes it sensitive to small changes in incoming and outgoing radiation. Small changes could put the temperature of the system to non- habitable conditions. To get better certainty in the model the design needs to be built and tested. Validerat; 20101217 (root)